2003
DOI: 10.1016/s0014-5793(03)00982-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Arabidopsis secretory phospholipase A2‐γ cDNA and its enzymatic properties1

Abstract: Plant secretory phospholipases A 2 (sPLA 2 s) probably play important roles in phospholipid signaling based on the data reported from other organisms, but their functions are poorly understood because of the lack of cloned sPLA 2 genes. In this study, we cloned and characterized an Arabidopsis secretory phospholipase A 2 -Q Q (AtsPLA 2 -Q Q) cDNA, and examined its enzymatic properties. The recombinant protein of AtsPLA 2 -Q Q showed maximal enzyme activity at pH 8.0, and required Ca 2þ for activity. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…The effect of enzyme immobilization on the sPLA 2 kinetics was also reported [31]. Description and kinetics properties of sPLA 2 from plants have been more frequent in their recombinant counterpart after an appropriate expression, purification and folding protocols [3,10,11,27,32] compared with their equivalent found in animals sPLA 2 s. The reason of this is due to the relative high amounts of the latter proteins found in their respective natural sources (venoms and pancreatic juice) and, therefore it allows an efficient purification. However, few studies using purified plant enzymes were reported from seeds of elm [9] and of soybean [33].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effect of enzyme immobilization on the sPLA 2 kinetics was also reported [31]. Description and kinetics properties of sPLA 2 from plants have been more frequent in their recombinant counterpart after an appropriate expression, purification and folding protocols [3,10,11,27,32] compared with their equivalent found in animals sPLA 2 s. The reason of this is due to the relative high amounts of the latter proteins found in their respective natural sources (venoms and pancreatic juice) and, therefore it allows an efficient purification. However, few studies using purified plant enzymes were reported from seeds of elm [9] and of soybean [33].…”
Section: Introductionmentioning
confidence: 94%
“…Both GmsPLA 2 enzymes displayed an optimum at 13e16 mN/m, a rather medium surface pressure, similar to that found for pancreatic sPLA 2 [56], if it is compared with the equivalent surface pressure estimated for phospholipids packed in bilayers calculated to be more than 31 mN/m by using theoretical approach [57]; or indirectly whereby lipolytic enzymes that are able to hydrolyze phospholipids of intact erythrocyte membranes hydrolyze lipid monolayers at above 31 mN/m [58]. The secretrory nature of sPLA 2 in plants has been elegantly tested checking the subcellular localization of Arabidopsis PLA 2 s with constructs of AtsPLA 2 s-green fluorescent protein fusions introduced into onion epidermal cells indicating that AtsPLA 2 s are secreted and accumulated mainly in the interstices of the extracellular space [10]. On the other hand, the expression levels of AtsPLA 2 s in A. thaliana is rather low and depends on the secreted isoforms in the different parts of the plants [42].…”
Section: Assay Of Pla 2 Activity On Langmuir Lipid Monolayers At Air mentioning
confidence: 99%
“…Four Arabidopsis PLA 2 isoforms (PLA 2 a, b, g, and d) have been identified and biochemically characterized Bahn et al, 2003;Ryu, 2004;Ryu et al, 2005). While the PLA 2 a and PLA 2 b genes are actively expressed in the root, PLA 2 g is expressed at relatively low levels in the root, and PLA 2 d is expressed exclusively in floral tissues .…”
Section: Pla 2 a Is Likely To Localize To The Golgimentioning
confidence: 99%
“…AtsPLA 2 g and AtsPLA 2 d also seem to be expressed only in flowers [57]. The activity of the AtsPLA 2 b promoter has been analysed and it appears that the AtsPLA 2 b gene is expressed in all tissues of actively growing seedlings, whereas in older plants, expression was observed mainly in vascular tissues and in flowers [4,55].…”
Section: Low Molecular Weight Secreted Phospholipases Amentioning
confidence: 99%